CSU-ALS protocol for cardiac arrest - Yadava, Om Prakash (Indian J Thorac Cardiovasc Surg, 2021)
Dr. O.P. Yadava, CEO & Chief Cardiac Surgeon, National Heart Institute, New Delhi, India and Editor-in-Chief, Indian Journal of Thoracic and Cardiovascular Surgery in conversation with Dr. Adrian J Levine, Consultant Cardiac Surgeon, University Hospital of the North Midlands, UK. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s12055-021-01221-1.